2023
DOI: 10.3389/fendo.2022.1077514
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic effect of NK1R antagonist in diabetic non-healing wound and depression

Abstract: Diabetes is a global disease with huge impacts on patients due to its complications, among which non-healing wounds and depression are common and challenging. The neurokinin 1 receptor (NK1R) inhibitor, aprepitant has been broadly applied for an antidepressant effect in depressive patients. Recent literature has indicated a therapeutic effect of downregulation in NK1R to diabetes-related fracture, cardiomyopathy, gastroparesis, and ocular surface disorders. In this study, differential expression genes in diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Our research revealed that reducing LHb neural activity enhanced both wound healing and depression-like behavior in diabetic mice ( Figure 5 ). In 2023, Li et al ( 2023 ) found that the blockade of NK1R may be therapeutic not only for depression but also for diabetic non-healing wounds. So, whether the activity of LHb is in some way related to this receptor will guide our future research work.…”
Section: Discussionmentioning
confidence: 99%
“…Our research revealed that reducing LHb neural activity enhanced both wound healing and depression-like behavior in diabetic mice ( Figure 5 ). In 2023, Li et al ( 2023 ) found that the blockade of NK1R may be therapeutic not only for depression but also for diabetic non-healing wounds. So, whether the activity of LHb is in some way related to this receptor will guide our future research work.…”
Section: Discussionmentioning
confidence: 99%